Delivery of dark material to Vesta via carbonaceous chondritic impacts - Reddy, Vishnu; Le Corre, Lucille; O’Brien, David P.; Nathues, Andreas; Cloutis, Edward A.; Durda, Daniel D.; Bottke, William F.; Bhatt, Megha U.; Nesvorny, David; Buczkowski, Debra; Scully, Jennifer E.C.; Palmer, Elizabeth M.; et al. (Icarus (New York, N.Y. 1962), 2012)
► Dark material on Vesta observed by Dawn is remnant carbonaceous chondrite impactor. ► Global abundance of carbonaceous chondrite material <6vol.% similar to howardites. ► Distribution of dark material suggests delivery during Veneneia basin formation event. ► Suggests extensive volatile delivery onto Vesta by carbonaceous impactors. ► First direct link between HED meteorites and surface of Vesta. NASA’s Dawn spacecraft observations of Asteroid (4) Vesta reveal a surface with the highest albedo and color variation of any asteroid we have observed so far. Terrains rich in low albedo dark material (DM) have been identified using Dawn Framing Camera (FC) 0.75μm filter images in several geologic settings: associated with impact craters (in the ejecta blanket material and/or on the crater walls and rims); as flow-like deposits or rays commonly associated with topographic highs; and as dark spots (likely secondary impacts) nearby impact craters. This DM could be a relic of ancient volcanic activity or exogenic in origin. We report that the majority of the spectra of DM are similar to carbonaceous chondrite meteorites mixed with materials indigenous to Vesta. Using high-resolution seven color images we compared DM color properties (albedo, band depth) with laboratory measurements of possible analog materials. Band depth and albedo of DM are identical to those of carbonaceous chondrite xenolith-rich howardite Mt. Pratt (PRA) 04401. Laboratory mixtures of Murchison CM2 carbonaceous chondrite and basaltic eucrite Millbillillie also show band depth and albedo affinity to DM. Modeling of carbonaceous chondrite abundance in DM (1–6vol.%) is consistent with howardite meteorites. We find no evidence for large-scale volcanism (exposed dikes/pyroclastic falls) as the source of DM. Our modeling efforts using impact crater scaling laws and numerical models of ejecta reaccretion suggest the delivery and emplacement of this DM on Vesta during the formation of the ∼400km Veneneia basin by a low-velocity (<2km/s) carbonaceous impactor. This discovery is important because it strengthens the long-held idea that primitive bodies are the source of carbon and probably volatiles in the early Solar System.